Simulasi Pengendalian Peralatan Perkantoran Menggunakan Jaringan Wi-Fi Berbasis Smart Office - M. Haris Surya (Institute of Information Technology and Social Science (IITSS), 2021)
The increasing level of human mobility has encouraged the development of various technological innovations to improve efficiency and comfort in daily activities, one of which is the use of Internet of Things (IoT) technology. This technology enables the control and monitoring of electronic devices remotely via an internet network. This study aims to simulate the control of office equipment using a Wi-Fi network based on the smart office concept. The system was simulated using Cisco Packet Tracer version 8.1 with devices including lights, air conditioners, fans, alarms, smoke detectors, and automatic doors. The network development method used was PPPPIOO (Prepare, Plan, Design, Implement, Operate, Optimize). The simulation results showed that all devices could be centrally controlled through mobile devices (smartphones), both within the local network and via the internet. The automated system was also able to respond to environmental conditions, such as activating fans and alarms when the smoke detector detected smoke above a certain threshold. These findings indicate that the IoT-based smart office concept is effective in improving the efficiency of office equipment management.